Bitumen modification using oil palm fruit ash for stone mastic asphalt - Rusbintardjo, Gatot (2011)
The objective of this study was to investigate the feasibility of using oil palm fruit ash (OPFA) as a bitumen modifier, to formulate the mix between OPFA and bitumen as a new binder with better physical and mechanical properties, and to evaluate the use of OPFA-modified bitumen (OPFA-MB) as a binder of stone mastic asphalt (SMA). In this study two sources of bitumen, bitumen B-1 and bitumen B-2 each had penetration grade 80/100 were modified by using OPFA. The bitumen was mixed with 2.5%, 5%, 7.5%, 10%, 12.5%, and 15% OPFA by weight of the bitumen at mixing temperature 160°C, mixing time 60 minutes, and mixing stirring speed 800 revolution per minute. There were two types of OPFA, Fine and Coarse-OPFA. Fine- OPFA was OPFA which had uniform particle size 75µm, and Coarse-OPFA was OPFA which had graded particle with maximum grains size 600µm. The bitumen mixed with OPFA was called OPFA-modified bitumen (OPFA-MB). There were four types of OPFA-MB namely Fine-OPFA-MB1, Coarse-OPFA-MB1, Fine- OPFA-MB2, and Coarse-OPFA-MB2. Each type of OPFA-MB had six OPFA content. For all of OPFA-MB penetration test at 25°C, softening point test, and viscosity test at 60°C and 135°C were conducted to determine penetration index (PI) and penetration-viscosity number (PVN). The results show that all OPFA-MB were not susceptible to the changes of temperature. Rheology test using dynamic shear rheometer (DSR), bending beam rheometer (BBR), and direct tension tester (DTT) show that OPFA-MB with the content of fine-OPFA 5%, 2, 5%, and 10% can withstand rutting at a temperature of 70°C, withstand fatigue cracking at a temperature of 20°C, and resist to thermal cracking at a temperature of -15°C. Using in stone mastic asphalt (SMA-14) mixtures resulted in higher Marshall stability than the minimum specification requirements. Resilient modulus, creep, and wheel tracking rutting tests show that OPFA-MB can strengthen SMA-14 mixtures. Static immersion test, boiling water and drain-down test show that OPFA-MB has good adhesion to bind aggregate. Based on penetration value and the results of rheology testing, OPFA-MB can be categorized as binder penetration grade 60/700 and Superpave bitumen grade PG 70 – 16. Overall test results suggest that OPFA is feasible to be used as modifier of the bitumen, and as a binder for stone mastic asphalt.